The impact of financial capital on the survival of start-ups in the Mekong delta region, Vietnam - An, Nguyen Van Vu; Ha, Nguyen Hong (Edelweiss Applied Science and Technology, 2024)
This study investigates the impact of financial capital on the survival of start-ups in Vietnam's Mekong Delta region, where new ventures face unique financial constraints due to limited access to formal funding and high reliance on informal sources. The study aims to determine how various types of financial capital—internal, informal, and formal—affect start-up survival rates and whether human capital factors such as founders' experience and education moderate these effects. Using a Cox Proportional Hazards Model, data were collected from 376 start-ups in the Mekong Delta through structured surveys. The findings reveal that formal financial capital significantly reduces failure risk, while informal and internal sources show limited influence. Human capital factors, especially work experience and education, further enhance survival prospects, underscoring their complementary role to financial capital. Additionally, the COVID-19 pandemic exacerbated financial challenges, highlighting the necessity for resilient funding sources. These results contribute to understanding the critical role of financial capital and human capital in supporting start-up survival, especially in economically constrained regions.